The effect of corporate governance on Islamic banking performance using maqasid index approach in Indonesia - Rahman, Audia Syafa’atur; Haron, Razali (2018)
Purpose – This study aims to provide the empirical evidence on the Maqasid performance of Islamic banks in relation to the Maqasid performance evaluation model, to examine the influence of SSB characteristics and board structures to IBs performance as measured by Maqasid performance evaluation model. Design/methodology/approach – Quantitative method used in this study. The simple additive weighting (TSAW) is employed to obtain the Maqasid Shariah achievement of IBs. The impact of SSB characteristics and board structures on IBs performance are tested using random-effects generalized least squares. Findings – Maqasid index for all the IBs in Indonesia within 2012 to 2016 ranged from above 11% to 28%. The Maqasid Syariah performance index where results reached above 20% are obtained by IBs such as BMI, BPS, and BBS. The consistent achievement above 23% are achieved by BMI. Other IBs such as BVS, BJBS, BBNS, BMS, BCAS, and MSI shows a fluctuating value of the Maqasid performance index every year. The random-effects generalized least squares result indicate that SSB characteristics (SSB size, SSB cross membership, SSB Education, and SSB reputation) and board structures (Board size and Board independence) have an essential role in improving the performance of IBs. The findings denote SSB with smaller size, higher portion of SSB cross membership, lesser SSB hold doctorate degree, lesser reputable scholar, more members on board of directors, and less independence non-executive directors will enhance the performance of IBs. Research limitations/implications – The weighting for each objective of the Maqasid performance index is only based on the literature review. Furthermore, the sample size is also limited by focusing on one country. Future research may extend the focus on examining the attributes of corporate governance such as the audit committees, the remuneration committees, and the ownership structures. In addition, the weighting of the Maqasid performance index has to accommodate the analysis on the relationships of the elements, which not only in one objective but also with other elements on the different objectives. Practical implications – The regulators should set up and impose a more robust and new tool to evaluate the Maqasid performance index in order to have an illustration on how far the role of IBs have contributed to the society. This will help the investors to have an informed decision which not only concentrate on the financial ratios but also the entire dimensions of IBs that reflect the main purpose of Islamic banks. Originality/value – The study examines the performance of Islamic banks using Maqasid evaluation performance model and contributes to the discussions on Maqasid performance. It is also highlighted the role of corporate governance on the achievement of Islamic banks Maqasid performance.